The Principles of Language Learning and Teaching in Communication Skill Developments - Dedi Aprianto; Novian Zaini (VELES Voices of English Language Education Society, 2019)
A language has two different and integrated skills, the receptive skills and the productive skills. Surprisingly, a speaking is a part of the productive one, as one of the main skills of all. It is also categorized as the micro ability salient for an effective communication and a global means of communication within both social interaction as well as digital communication. The development of the micro ability must have been considered by paying attention toward the principles of language learning and teaching; needs-based curriculum, learning methods, and the theoretical basis construction. The strong consideration of the basic principles of language and teaching gives the nuance and the insights towards both language teachers, curriculum makers, as well. The use of Communicative Language Teaching (CLT) reflected from what is rooted in Hymes’ theory emphasizes on Communicative Competence as a social interaction and functional rules of human language (Constructivism Theory). Whereas the Chomsky’s notion of Communicative Competence based on the psycholinguistic perspective depicting a language has two concepts, namely competence and performance (Nativist Theory). Finally, a language is seen as a phenomena observable and even process of automaticity. It focuses on the relationship of stimuli-responses by strengthening that relationship through more exercises / practices.